2015
DOI: 10.3389/fncel.2015.00052
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Retinoblastoma (Rb)1-inducible dominant-negative (DN) mouse model

Abstract: Retinoblastoma 1 (Rb1) is an essential gene regulating cellular proliferation, differentiation, and homeostasis. To exert these functions, Rb1 is recruited and physically interacts with a growing variety of signaling pathways. While Rb1 does not appear to be ubiquitously expressed, its expression has been confirmed in a variety of hematopoietic and neuronal-derived cells, including the inner ear hair cells (HCs). Studies in transgenic mice demonstrate that complete germline or conditional Rb1 deletion leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Focusing on genes that are altered both during development and regeneration, the enrichment of E2F noted indicates the presence of proliferation in the cochlea at the relevant period of development. Given the role of this TF family in inducing proliferation, their involvement in hair cell regeneration is not surprising and is currently the focus of active research [ 43 ]. In contrast, ZF5 is known primarily as a repressor of transcription and specifically as a regulator of cell cycle progression (through c-myc [ 44 ]), and cognitive development (through FMR1 [ 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on genes that are altered both during development and regeneration, the enrichment of E2F noted indicates the presence of proliferation in the cochlea at the relevant period of development. Given the role of this TF family in inducing proliferation, their involvement in hair cell regeneration is not surprising and is currently the focus of active research [ 43 ]. In contrast, ZF5 is known primarily as a repressor of transcription and specifically as a regulator of cell cycle progression (through c-myc [ 44 ]), and cognitive development (through FMR1 [ 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In general, many drug candidates are poorly characterized in terms of their ability to cross the BLB and their pharmacokinetics and pharmacodynamics (PK/PD) in the inner ear fluids. For example, doxycycline cannot effectively penetrate into the cochlea of adults (Cox et al, 2014a; Walters et al, 2015a), despite several reports to the contrary (Kelly et al, 2012; Tarang et al, 2015). Moreover, Dox is not easily cleared by the inner ear fluids after it does get in (Cox et al, 2014a; Walters et al, 2015a).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Retinoblastoma 1 (RB1) is an endogenous protein that regulating cellular proliferation and differentiation. Downregulation of RB1 was reported to increase the proliferation of hair cells in the cochlea [49]. Findings which have recently emerged have shown that epigenetic mechanisms may also play important roles in controlling stem cell states, and such regulation might also have effects on tissue regeneration [50].…”
Section: A) Endogenous Stem Cellmentioning
confidence: 99%